KORELASI PENGUASAAN KOSAKATA BIDANG LINGKUNGAN HIDUP DENGAN KETERAMPILAN MENULIS TEKS BERITA SISWA KELAS VIII MTs.N 2 PESISIR SELATAN - Rahmi, Restina; Basri, Irfani (Universitas Negeri Padang, 2019)
ABSTRACTÂ The purpose of this research there are three. First, describe the environmental field vocabulary mastery of grade VIII MTs.N. 2 southern coast. Second, it describes the writing skills text beritasiswa class VIII MTs.N. 2 SelatanKetiga Coast, describing the correlation field environmental vocabulary mastery with the text of the news writing skills of students of class VIII MTs.N. 2 southern coast. This research type is quantitative descriptive method. The design used is a korelasional design. Population research is grade VIII MTs.N 2 southern coast that are listed in the 2018/2019, i.e., 223 students. The research sample is determined by proportional random sampling of 20% of the population, namely 45 pupils. The results of the research there are three. First, mastery of the vocabulary of the field of the environment students of class VIII MTs.N 2 located on the southern coast of qualifications either (B) with an average value of 78.81. Secondly, the text of the news writing skills of students of class VIII MTs.N. 2 located on the southern coast of qualifications either (B) with an average of 79.54. Third, there is a correlation of mastery of the vocabulary of the field of the environment with the text of the news writing skills of students of class VIII MTs.N 2 southern coast on a 95% confidence level with n-2 degrees of freedom. the value of thitung > ttabel (5.01 > 1.68).Â Kata Kunci: Korelasi, Kotakata Bidang Lingkungan Hidup, Menulis, Teks Berita